НАВОИЙ ВИЛОЯТИ СУҒОРИЛАДИГАН СУР ТУСЛИ ҚЎНҒИР ЎТЛОҚЛИ ТУПРОҚЛАРИНИНГ ТУПРОҚ-МЕЛИОРАТИВ ТАВСИФИ - Кушаков, А.Ж. (SCIENCE and SOCIETY, 2020)
Under the influence of various natural factors salinization processes are occurring in the gray-brown-meadow gypsum soils in the foothills of desert regions. The article discusses the necessity of preventing and studying the soil salinization processes, in order to improve the reclamation of lands, to increase soil fertility and develop methods for their rational use.
Keywords: reclamation; soil; geomorphology; salinization; humus; phosphorus; gray brown meadow; lithology; gypsum; agrotechnical